C. R. a. Van Bommel (1829-1852) En Het Middelbaar Onderwijs in Het Bisdom Luik: C. R. A. van Bommel, 1829-52, and secondary education in the diocese of Liège. - Hanson, Marc B. (1993)
When C. R. A. van Bommel was appointed bishop of Liège in 1829, the state of secondary education in his diocese after the turbulent period of 1795-1830 gave cause for great concern. The prelate, highly experienced in the field of education, at once set out to approach the problems from his own educational-religious point of view. After about ten years, the clergy already had a firm grip on an important part of the field. In its attempt to raise the level of education, the classical languages were given absolute priority but some attention was also paid to subsidiary subjects such as modern languages and the sciences. At that time, most of the colleges included a boarding school. The views of the Liège bishop on life at such schools were very refreshing for those days. He felt that a boarding school should not be a stuffy, uninspiring prison but a pleasant, big home where younger and older pupils could live together in a relaxed and unconstrained manner. Van Bommel was concerned about their health and well-being and that of the entire staff. This dynamic bishop, more than anyone else, put a lasting stamp on secondary education in his diocese.
Keywords: Belgium (Liège diocese); Bommel, C. R. A. van; secondary education